2019
DOI: 10.21873/cgp.20161
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Primary Colon Cancer and Synchronous Solitary Liver Metastasis

Abstract: Background/Aim: Colon cancer is prone to distant metastases to other sites and the risk of recurrence is relatively high. Therefore, the identification of liver metastasis-related factors is important for the diagnosis or treatment of colon cancer. The aim of this study was to identify the metastasis-related factors that are differentially expressed in synchronous solitary liver metastasis compared to primary colon cancer. Materials and Methods: Tissues of primary colon cancer and associated with liver metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Many patients subsequently develop metastases soon after diagnosis which drastically impacts their prognosis. [ 6 ] Patients without metastasis can largely be cured by resection of the primary tumor and have a 5‐year survival rate exceeding 80%. In contrast, patients with lymph node metastases have a 5‐year survival rate below 50%, and the presence or absence of regional lymph node metastasis influences the chosen therapeutic regimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients subsequently develop metastases soon after diagnosis which drastically impacts their prognosis. [ 6 ] Patients without metastasis can largely be cured by resection of the primary tumor and have a 5‐year survival rate exceeding 80%. In contrast, patients with lymph node metastases have a 5‐year survival rate below 50%, and the presence or absence of regional lymph node metastasis influences the chosen therapeutic regimen.…”
Section: Introductionmentioning
confidence: 99%
“…[13] On this basis, proteomic analyses have been applied to CRC in order identify diagnostic biomarkers and new therapeutic targets. [12,17,18] Previous proteomic analyses of CRC have variously defined differentially expressed proteins (DEPs) associated with the advancement of CRC, [1,2,6,12] with one study analyzing a single case of primary colon cancer and its synchronous liver metastasis. [6] Notwithstanding the findings of such studies, more work is still required to provide candidate CRC biomarkers as well as gaining better insights into its tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, ECM remodeling plays a crucial role in the formation of tumor and organ specific premetastatic niches and the adjustment of disseminated tumor cells to distant organs [9]. A recent study by Kim et al identified 58 differentially regulated proteins in CRC primary tumors and their respective solitary synchronous CRLM of which many were associated with the ECM [10], suggesting a crucial role of ECM proteins in colorectal cancer liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Kim et al . identified 58 differentially regulated proteins in CRC primary tumors and their respective solitary synchronous CRLM of which many were associated with the ECM [ 10 ], suggesting a crucial role of ECM proteins in colorectal cancer liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The monoclonal antibodies like cetuximab, panitumumab, and bevacizumab have demonstrated effectiveness, both in terms of better response and improved survival. A comparison of various markers between primary and metastatic tumors have been recently reported [9][10][11][12][13]. Previous studies reported that while the immune microenvironment in the primary CRC tumor and liver metastasis is different, hypoxia-inducible factor-1α (HIF-1α) expression in primary CRC was comparable to that in corresponding metastases and HIF-1α expression is consistent in primary CRC and matched metastatic tissues [9,10].…”
Section: Introductionmentioning
confidence: 99%